Fluorescence probe for hypochlorous acid in water and its applications for highly lysosome-targetable live cell imaging - Jiao, Xiaojie; Liu, Chang; Wang, Qing; Huang, Kun; He, Song; Zhao, Liancheng; Zeng, Xianshun (Analytica chimica acta, 2017)
Hypochloric acid (HOCl) plays important roles in cell signaling and homeostasis, such as anti-inflammation and immune regulation, pathogen response and so on. Accordingly, direct detection of HOCl at the organelle level is important for investigation of the complex contributions of HOCl to human health. In the present study, a water soluble lysosome-targeting fluorescent probe Lyso-1 bearing a hydrazone moiety as a HOCl-responsive site and a morpholine unit as a lysosomal-targeting group has been synthesized and evaluated for its ability to image lysosomal HOCl. The probe Lyso-1, based on a novel HOCl-promoted hydrazone oxidation strategy, showed a highly selective fluorescent off/on response to HOCl with the various reactive oxygen species in water. With increasing amount of ClO− from 0.5 to 2.5 μM, a linear correlation between the fluorescence intensity (570 nm) of Lyso-1 and [ClO−] was found, and the regression equation was y = 96.65 + 110.2068[ClO−] with a linear coefficient R of 0.9920. The detection limit is determined to be 60 nM. Lyso-1 demonstrated a perfect lysosomal targetable ability, and was successfully applied to image of exogenous, endogenous produced lysosomal HOCl in live L929 cells. The success of subcellular imaging indicated that the lysosome-targetable probe Lyso-1 could be used in further applications for the investigation of biological functions and pathological roles of HClO at organelle levels. [Display omitted] •A lysosomal-targeting probe Lyso-1 has been synthesized for lysosomal HOCl imaging.•The probe showed a highly selective fluorescent off/on response to HOCl in water.•The probe demonstrated a perfect lysosomal targetable ability.•The probe has been successfully applied to image of lysosomal HOCl in live L929 cells.